2021
DOI: 10.2209/tdcpublication.2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Orthodontic Treatment for Generalized Aggressive Periodontitis

Abstract: Aggressive periodontitis mostly affects young people, causing rapid destruction of periodontal tissue and loss of supporting alveolar bone. The destruction of periodontal tissue induces pathological tooth movement, resulting in various types of malocclusion such as crowding or spacing in the dentition. This report describes orthodontic treatment for malocclusion due to generalized aggressive periodontitis. The patient was a 31-year-old woman who presented with the chief complaint of displacement in the anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
(15 reference statements)
0
11
0
3
Order By: Relevance
“…Currently, the main treatment options for anterior tooth displacement due to periodontal disease include conventional periodontal therapy, medication, periodontal tissue regeneration, and surgery. Previous studies have shown that it is di cult to achieve the desired clinical outcome using conventional treatment [4]. Orthodontic treatment is used clinically in patients with anterior tooth displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the main treatment options for anterior tooth displacement due to periodontal disease include conventional periodontal therapy, medication, periodontal tissue regeneration, and surgery. Previous studies have shown that it is di cult to achieve the desired clinical outcome using conventional treatment [4]. Orthodontic treatment is used clinically in patients with anterior tooth displacement.…”
Section: Introductionmentioning
confidence: 99%
“…Attia et al 20 visualizaron resultados regenerativos favorables después del tratamiento de ortodoncia en comparación con un enfoque diferido después de 2 meses Además, se cree que el movimiento dental de ortodoncia crea una inflamación transitoria en la pulpa y que la pulpa se recupera durante el tiempo necesario para crear extensa reabsorción radicular. 21 Se ha vinculado la reabsorción radicular de 1 a 3 mm en la intrusión de incisivos en pacientes adultos que muestran pérdida de hueso marginal y sobremordida profunda. Reichert C. et al, 21 en su trabajo en pacientes de 12 años, indicaron que la ortodoncia ya no es…”
Section: Fuerzas Ortodónticasunclassified
“…21 Se ha vinculado la reabsorción radicular de 1 a 3 mm en la intrusión de incisivos en pacientes adultos que muestran pérdida de hueso marginal y sobremordida profunda. Reichert C. et al, 21 en su trabajo en pacientes de 12 años, indicaron que la ortodoncia ya no es…”
Section: Fuerzas Ortodónticasunclassified
“…Die kieferorthopädische Phase muss durch eine stetige Kontrolle der Mundhygiene und des Parodontalstatus durch den Pardodontologen begleitet werden 44 . Hierbei sollte, um den entzündungsfreien Zustand während der Therapie aufrechtzuerhalten, eine regelmäßige Mundhygieneinstruktion sowie eine professionelle Reinigung erfolgen.…”
Section: Behandlungspfad Bei Parodontal Vorgeschädigten Patientenunclassified